All Days 2015
DOI: 10.2118/174237-ms
|View full text |Cite
|
Sign up to set email alerts
|

Formation Damage in Tight Gas Reservoirs

Abstract: The increased demand for more sources of clean energy such as natural gas from unconventional reservoirs has forced the industry to explore the more challenging tight gas reservoirs. Tight gas reservoirs constitute a significant proportion of the world's natural gas resource and offer great potential for future reserve growth and production. However, to meet future global energy demand, access to tight gas reservoirs requires innovative and cost effective technical solutions.Yet, tight gas reservoirs are often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…74 In such a scenario, underbalanced drilling (UBD) is helpful because, in place of heavy drilling fluids and muds, a light mineral oil, 75 nitrogen foam, 76 and sometimes compressed air 77 are used to achieve underbalanced well conditions and the low density of such drilling fluids will cause the hydrostatic pressure in the wellbore to be lower than the internal fluid pressure of that formation, resulting in the production of reservoir fluids while drilling. 78 However, the density of these fluids is not sufficient enough to generate enough torque for the bottom-hole motors to rotate at its maximum efficiency. 79 Fortuitously, SC-CO 2 , because of its liquidlike density, is able to provide sufficient power to rotate the down-hole motor.…”
Section: Sc-co 2 -Based Drillingmentioning
confidence: 99%
See 1 more Smart Citation
“…74 In such a scenario, underbalanced drilling (UBD) is helpful because, in place of heavy drilling fluids and muds, a light mineral oil, 75 nitrogen foam, 76 and sometimes compressed air 77 are used to achieve underbalanced well conditions and the low density of such drilling fluids will cause the hydrostatic pressure in the wellbore to be lower than the internal fluid pressure of that formation, resulting in the production of reservoir fluids while drilling. 78 However, the density of these fluids is not sufficient enough to generate enough torque for the bottom-hole motors to rotate at its maximum efficiency. 79 Fortuitously, SC-CO 2 , because of its liquidlike density, is able to provide sufficient power to rotate the down-hole motor.…”
Section: Sc-co 2 -Based Drillingmentioning
confidence: 99%
“…Traditionally, water-based fluids were used for drilling tight gas reservoirs for the recovery of oil and gas resources. , However, unconventional reservoirs vulnerable to formation damages are not ideal to drill with water-jets because it can cause excessive overbalance condition near the bottom hole, resulting from the hydrostatic pressure exerted by the produced mud . In such a scenario, underbalanced drilling (UBD) is helpful because, in place of heavy drilling fluids and muds, a light mineral oil, nitrogen foam, and sometimes compressed air are used to achieve underbalanced well conditions and the low density of such drilling fluids will cause the hydrostatic pressure in the wellbore to be lower than the internal fluid pressure of that formation, resulting in the production of reservoir fluids while drilling . However, the density of these fluids is not sufficient enough to generate enough torque for the bottom-hole motors to rotate at its maximum efficiency .…”
Section: Sc-co2-based Drillingmentioning
confidence: 99%
“…The global demand for oil and natural gas resources is increasing daily, which brings a great challenge to the oil and natural gas companies due to the increasing difficulties of well drilling and completion, especially for the exploration and development of low permeability of oil and gas fields. The development of low permeability reservoirs has become a major trend presently. With the continuous improvement of exploration technology, the quality of the newly developed oil and gas reservoirs will become worse and worse, and the proportion of low permeability reserves will become higher and higher. In low permeability reservoirs, the formation is very vulnerable to pollution and damage, and the production of oil and gas wells is low due to the tight cementation, muddy and fine minerals, low porosity, stress sensitivity, and low effective permeability. Therefore, it is very important to protect reservoirs, reduce and avoid pollution for long-term development, and stable production of low permeability oil and gas fields. …”
Section: Introductionmentioning
confidence: 99%
“…The small size of these pores and throats increases the susceptibility of the reservoir to secondary damage caused by the fracturing fluids (FFs). Extensive research has demonstrated that physical and chemical damage are the primary types of damage in tight reservoirs, which can be attributed to various mechanisms including fluid sensitivity, intrusion by solid particles, phase trapping, sensitivity to stress, and adsorption of treatment agents. …”
Section: Introductionmentioning
confidence: 99%